State of Component Models Usage: Justifying the Need for a Component Model Selection Framework - Aris, H.; Salim, S. (2011)
The presence of a large number of component models has caused some difficulties in selecting suitable component models to be used, either for research purpose or for software development purpose. Lack of framework or standard that can be used to guide the process of selecting suitable component models is believed to be one of the reasons that have caused the difficulties. Therefore, in this article, the need for a component model selection framework is justified. The selection framework can be applied by the software developers to help them determine suitable component models to be used in their software development projects. Possible contributions of the framework to the research and software development industry communities are also identified. These are achieved by examining the current state of component models usage in both research and software development industry communities, which are obtained from a number of related resources found from exhaustive literature search.